The Economic Impact Of Quicksilver Cruise On The Income Of Mega Pontoon Employees In Toyapakeh Village - Putu Yurika Selly Novia; I Gusti Putu Bagus Sasrawan Mananda; I Ketut Antara (International Journal of Technology and Education Research, 2025)
This study aims to analyze the economic impact of Mega ponton Quicksilver Cruise marine tourism on the income of Mega ponton employees in Toyapakeh Village, Nusa Penida District, Klungkung Regency. This research employs a mixed-method approach, using qualitative methods to describe the existing tourism activity conditions and quantitative methods to measure the economic impact through comparative analysis and multiplier effect analysis. The sample consists of 100 tourist respondents and 25 Mega ponton employees. Data collection techniques include observation, interviews, questionnaires, and documentation studies. The results show that the Mega ponton tourism activity has become a main attraction, supported by various facilities such as the Mega ponton attraction itself, good accessibility, marine tourism support infrastructure, accommodations, cafés/restaurants, souvenir shops, as well as support from local institutions such as BUMDes and the Coral Triangle Center (CTC). The characteristics of tourists are predominantly female, aged 26–35 years, highly educated, from foreign countries, and visiting with family or friends. All Mega ponton employees in Toyapakeh Village are local residents. The monthly income of Mega ponton Quicksilver Cruise reaches IDR 300,000,000. Economically, the total tourist expenditure reaches IDR 241,000,000 per month, with a direct impact of IDR 300,000,000, an indirect impact of IDR 192,400,000, and an induced impact of IDR 72,750,000. The Keynesian Income Multiplier value is 2.35, the Ratio Income Multiplier Type I is 1.64, and Type II is 1.88, indicating that this marine tourism activity contributes significantly to the increase in Mega ponton employee income and the economic circulation in Toyapakeh Village. Therefore, well-managed marine tourism development can serve as a key driver in advancing the coastal community’s economic development.